Burkina Faso : Poverty Reduction Strategy Paper Progress Report-Joint Staff Assessment. (IMF Staff Country Reports; Country Report ;, 2004)
Despite severe exogenous shocks, the macroeconomic program remained broadly on track, and several social indicators, particularly in the area of basic education, progressed. A variety of measures have been successfully implemented to improve the environment for private sector development, reduce the vulnerability of the rural sector, and strengthen public finance management. A more comprehensive framework for growth-enhancing policies should encompass the rural sector; foster the development of analytical links between budgets and results; and strengthen the role of the Poverty Reduction Strategy Paper (PRSP) as an integrative framework for sectoral policies.